KNOWLEDGE DIALOGUE AS A HUMAN POSITION TOWARD “THE OTHER”: ONTOLOGICAL AND PEDAGOGICAL BACKGROUND FOR HEALTH EDUCATION - Bastidas Acevedo, Miriam; Pérez Becerra, Francy Nelly; Torres Ospina, Julio Nicolás; Escobar Paucar, Gloria; Arango Córdoba, Adriana; Peñaranda Correa, Fernando (Investigación y Educación en Enfermería, 2009)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> This article presents an alternative proposal to the traditional model, based in a “knowledge dialogue”. More than a pedagogical proposal, “knowledge dialogue” is a position based on respectful and democratic relations and practices, which recognizes the pupil as a subject, responsible of its own destiny, and human beings as not finished beings that construct themselves interacting with others and the world. “Knowledge dialogue” is a communicative process in which there is an interaction between two rationalities, scientific and daily knowledge, trying to understand each other. It implies the recognition of the “other” as someone different, with diverse knowledge and positions. It doesn’t deny that health education has an intention, directed to promote autonomy and liberty, so that each person can take the most appropriate decisions according to its own context and situation. It is a scene where different knowledge, truths, feelings and rationalities play, in the construction of consensus, but respecting disagreement. It is a meeting among human beings – pupil and teacher – where both construct and strengthen themselves. It is a dialogue in which both of them are transformed.